Ketamine in palliative care: an updated systematic review - Kinga Dowierciał; Joanna Wziątek; Piotr Kowalik; Daria Krzyżanowska; Patrycja Fatyga; Wiktoria Fatyga; Gabriela Pabis; Paula Bętkowska; Iwona Koziołek; Magdalena Strzelczyk (Quality in Sport, 2025)
Introduction